ANALISIS PERBANDINGAN PEMAKAIAN SEMEN TONASA DAN SEMEN CONCH TERHADAP KUAT TEKAN BETON - Istia, Ris Viko; Huwae, David Daniel Marthin; Tahya, Hendrie (Journal Agregate, 2023)
This research was conducted to test the comparison of compressive strength of concrete using Tonasa cement and Conch cement. Remembering that cement is the most important material in making concrete. So many people use Portland cement in making concrete. The aim of this research is to determine the compressive strength of concrete that is good for use in construction work. In this research, Tonasa cement and Conch cement were used to determine the compressive strength of concrete at the age of 3 days and 7 days in the Ambon State Polytechnic laboratory, civil engineering department. With 12 cylindrical test objects with a diameter of 15 cm and a height of 30 cm. The method used in this research is an experimental method, to investigate the relationship between the compressive strength of compression testing machine concrete and the hammer test number test. the result showed that the  average compressive strength is : Tonasa cement was 41.52 Mpa for cylindrical concrete, 500.23  for cube concrete at 3 days old and 28.16 MPa for cylindrical concrete, 339.32  for cube concrete at 7 days and Conch cement of 38.92 Mpa for cylindrical concrete, 468.97  for cube concrete at 3 years of age. days, and 26.86 MPa for cylindrical concrete, 323.58  for cube concrete at the age of 7 days.